Phytoremediation of molybdenum (Mo)-contaminated soil using plant and humic substance - Mengmeng Wang; Gangfu Song; Zhihong Zheng; Zhixin Song; Xiao Mi (Ecotoxicology and Environmental Safety)
The severity of soil molybdenum (Mo) pollution is increasing, and effective management of contaminated soil is essential for the sustainable development of soil. To investigate this, a pot experiment was carried out to assess the impact of different rates of humic acid (HA) and fulvic acid (FA) on the mobility of Mo in soil solution and its uptake by alfalfa, wheat and green bristlegrass. The concentration of Mo in Plants and soil was determined using an Atomic Absorption Spectrophotometer. The findings revealed that the application of HA led to an increase in Mo accumulation in the shoot and root of green bristlegrass and wheat, ranging from 10.56 % to 28.73 % and 62.15–115.79 % (shoot), and 17.52–46.53 % and 6.29-81.25 % (root), respectively. Nonetheless, the use of HA resulted in a slight inhibition of plant Mo uptake, leading to reduced Mo accumulation in alfalfa roots compared to the control treatment (from 3284.49 mg/kg to 2140.78–2813.54 mg/kg). On the other hand, the application of FA decreased Mo accumulation in the wheat shoot (from 909.92 mg/kg to 338.54–837.45 mg/kg). Furthermore, the bioavailability of green bristlegrass (with HA) and wheat (with FA) decreased, and the percentage of residual fraction of Mo increased (from 0.39 % to 0.78–0.96 %, from 3.95 % to 3.97∼ 4.34 %). This study aims to elucidate the ternary interaction among Mo, humic substances, and plants (alfalfa, wheat, and green bristlegrass), to enhance both the activation and hyperaccumulation of Mo simultaneously.